Tailorable infrared emission of microelectromechanical system-based thermal emitters with NiO films for gas sensing - Li, Nanxi (2022)
Infrared gas sensors hold great promise in the internet of things and artificial intelligence. Making infrared light sources with miniaturized size, reliable and tunable emission is essential but remains challenging. Herein, we present the tailorability of radiant power and the emergence of new emission wavelength of microelectromechanical system (MEMS)-based thermal emitters with nickel oxide (NiO) films. The coating of NiO on emitters increases top surface emissivity and induces the appearance of new wavelengths between 15 and 19 µm, all of which have been justified by spectroscopic methods. Furthermore, a sensor array is assembled for simultaneous monitoring of concentrations of carbon dioxide (CO2), methane (CH4), humidity, and temperature. The platform shows selective and sensitive detection at room temperature toward CO2 and CH4 with detection limits of around 50 and 1750 ppm, respectively, and also shows fast response/recovery and good recyclability. The demonstrated emission tailorability of MEMS emitters and their usage in sensor array provide novel insights for designing and fabricating optical sensors with good performance, which is promising for mass production and commercialization.